Characterisation of Waterborne Psychrophilic Massilia Isolates with Violacein Production and Description of Massilia antarctica sp. nov. - Ivo Sedláček; Pavla Holochová; Hans-Jürgen Busse; Vendula Koublová; Stanislava Králová; Pavel Švec; Roman Sobotka; Eva Staňková; Jan Pilný; Ondrej Šedo; Jana Smolíková; Karel Sedlář (Microorganisms, 2022)
A group of seven bacterial strains producing blue-purple pigmented colonies on R2A agar was isolated from freshwater samples collected in a deglaciated part of James Ross Island and Eagle Island, Antarctica, from 2017–2019. The isolates were psychrophilic, oligotrophic, resistant to chloramphenicol, and exhibited strong hydrolytic activities. To clarify the taxonomic position of these isolates, a polyphasic taxonomic approach was applied based on sequencing of the 16S rRNA, gyrB and lepA genes, whole-genome sequencing, rep-PCR, MALDI-TOF MS, chemotaxonomy analyses and biotyping. Phylogenetic analysis of the 16S rRNA gene sequences revealed that the entire group are representatives of the genus Massilia. The closest relatives of the reference strain P8398T were Massilia atriviolacea, Massilia violaceinigra, Massilia rubra, Massilia mucilaginosa, Massilia aquatica, Massilia frigida, Massilia glaciei and Massilia eurypsychrophila with a pairwise similarity of 98.6–100% in the 16S rRNA. The subsequent gyrB and lepA sequencing results showed the novelty of the analysed group, and the average nucleotide identity and digital DNA–DNA hybridisation values clearly proved that P8398T represents a distinct Massilia species. After all these results, we nominate a new species with the proposed name Massilia antarctica sp. nov. The type strain is P8398T (= CCM 8941T = LMG 32108T).